SKEMA INOVATIF PEMENUHAN KESEJAHTERAAN ATAS PAPAN - Budi Prayitno; Arif Kusumawanto; Didik Kristiadi; Suryanto Suryanto (Universitas Gadjah Mada, 2016)
This study uses cross-case analysis, this study aims to provide an innovation on housing policy which is frequently fail. Housing becomes a part of the basic needs for all citizen, especialy for those who have low incomes and poor citizens as mandated on the State constitution. The decentralization era is threathenedby a massive intervention of the Central Government which only creates the Local Government to be a charity chain and burden its potential innovation of both institutions and partnerships. Besides that, housing is a part of city. Therefore, it is necessary to build a strong relationship between fulfilling theneed of housing and the concept of urban planning